2019
DOI: 10.17675/2305-6894-2019-8-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids as green and environmental benign corrosion inhibitors: An overview

Abstract: Alkaloids are naturally occurring nitrogen containing organic bases that possess diverse and significant physiological effects on animals and humans. They are mostly derived from the plants. Because of their natural and biological origin, they (alkaloids) are considered as environmental benign alternatives to be used as corrosion inhibitors at the place of traditional and toxic synthetic corrosion inhibitors. Numerous alkaloids have been employed as effective corrosion inhibitors for metals and alloys in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 96 publications
0
2
0
1
Order By: Relevance
“…On the other hand, the corrosion inhibition mechanism occurs through the adsorption of the inhibitors ions/molecules on the corroding metal/alloy surfaces to form more stable films. Past researches had reported that some organic [20][21][22][23][24][25] and inorganic [26][27][28][29][30] compounds were used as eco-friendly corrosion inhibitors because they form complexes with metal ions on metal/alloy surface. Investigations of corrosion-inhibiting ability of inorganic radicals or ions, e.g., nitrites, molybdates, tungstates, polyphosphates are now being increasingly used as eco-friendly inhibitor due to their zero-toxic nature [10,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the corrosion inhibition mechanism occurs through the adsorption of the inhibitors ions/molecules on the corroding metal/alloy surfaces to form more stable films. Past researches had reported that some organic [20][21][22][23][24][25] and inorganic [26][27][28][29][30] compounds were used as eco-friendly corrosion inhibitors because they form complexes with metal ions on metal/alloy surface. Investigations of corrosion-inhibiting ability of inorganic radicals or ions, e.g., nitrites, molybdates, tungstates, polyphosphates are now being increasingly used as eco-friendly inhibitor due to their zero-toxic nature [10,[31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Investigasi inhibitor korosi berbasis ekstrak bahan alam (green inhibitor) terus berkembang karena bersifat ramah lingkungan, renewable, biodigradable, tidak menimbulkan polutan, tidak beracun, mudah diproduksi, murah, dan memiliki efisiensi anti korosi yang tinggi [28], [29]. Green inhibitor yang dalam struktur senyawanya mengandung cincin aromatik dan gugus heteroatom (seperti O, N, S, P) dianggap sebagai inhibitor yang efekif dan [30]- [32].…”
Section: Green Inhibitor Korosiunclassified
“…Changes in the structure of the surface layer on the metal induce changes in the parameters, such as impedance and phase angle, so their increase indicates the formation of a layer that protects the surface. According to several review papers published regarding corrosion inhibitors and with special attention devoted to the eco-friendly corrosion inhibitors, they are now quite numerous [3][4][5][6], and purine derivatives present an important class of alkaloids studied as corrosion inhibitors [7]. Xanthines are bioorganic compounds that are a very common constituent of numerous foods and drinks, such as coffee, tea, cocoa, chocolate, etc.…”
Section: Introductionmentioning
confidence: 99%